The Final Months of Massive Star Evolution from the Circumstellar Environment around SN Ic 2020oi - Maeda, Keiichi (2021)
We present the results of Atacama Large Millimeter/submillimeter Array (ALMA) band 3 observations of the nearby type Ic supernova (SN) 2020oi. Under the standard assumptions on the SN-circumstellar medium (CSM) interaction and the synchrotron emission, the data indicate that the CSM structure deviates from a smooth distribution expected from the steady-state mass loss in the very vicinity of the SN (≲1015 cm), which is then connected to the outer smooth distribution (⪆1016 cm). This structure is further confirmed through the light-curve modeling of the whole radio data set as combined with the previously reported data at lower frequency. Because this is an explosion of a bare carbon-oxygen (C+O) star with a fast wind, we can trace the mass-loss history of the progenitor of SN 2020oi in the final year. The inferred nonsmooth CSM distribution corresponds to fluctuations on the subyear timescale in the mass-loss history toward the SN explosion. Our finding suggests that the pre-SN activity is likely driven by the accelerated change in the nuclear burning stage in the last moments just before the massive star´s demise. The structure of the CSM derived in this study is beyond the applicability of the other methods at optical wavelengths, highlighting the importance and uniqueness of quick follow-up observations of SNe by ALMA and other radio facilities.